2015
DOI: 10.1039/c4nr07243j
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of electrospun MFe2O4(M = Co, Ni, Cu, Mn) spinel nanofibers with excellent electrocatalytic properties for oxygen evolution and hydrogen peroxide reduction

Abstract: Designing and preparing porous transition metal ferrites without using any template, shape-directing agent, and surfactant is a challenge. Herein, heterojunction MFe2O4 (M = Co, Ni, Cu, Mn) nanofiber (NF) based films with three-dimensional configurations were synthesized by electrospinning and the subsequent thermal treatment processes. Characterization results indeed show the 3D net-like textural structures of the electrospun spinel-type MFe2O4 NFs. In particular, the resulting MFe2O4 NFs have lengths up to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 466 publications
(214 citation statements)
references
References 45 publications
6
206
1
1
Order By: Relevance
“…33 In the highresolution spectrum of Co 2p ( Figure 3C, blue and magenta lines), the binding energy of the peaks at 780.96 eV and 783.22 eV are attributed to Co 2p 3/2 , indicating the presence of Co (II) and Co (III) species in FeNiCo LDH. 34 It's worth noting that besides the peak for Fe (III) (710.78 eV, Figure 3D, blue line), another peak appeared at binding energy of 712.78 eV ( Figure 3D, magenta line), suggesting the existence of Fe (IV) in the material. 35 Boettcher et al 36 demonstrated that Fe affects the local electronic structure of NiOOH and may serve as the active site.…”
Section: Resultsmentioning
confidence: 99%
“…33 In the highresolution spectrum of Co 2p ( Figure 3C, blue and magenta lines), the binding energy of the peaks at 780.96 eV and 783.22 eV are attributed to Co 2p 3/2 , indicating the presence of Co (II) and Co (III) species in FeNiCo LDH. 34 It's worth noting that besides the peak for Fe (III) (710.78 eV, Figure 3D, blue line), another peak appeared at binding energy of 712.78 eV ( Figure 3D, magenta line), suggesting the existence of Fe (IV) in the material. 35 Boettcher et al 36 demonstrated that Fe affects the local electronic structure of NiOOH and may serve as the active site.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that the role of Fe in OER activity is to www.advenergymat.de modulate the porosity of the material and change the electronic structure of the material. [135] …”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Mn-based catalyst is beneficial to keep 3D net-like structure. The distinctive structure may bring more advantages, such as large specific surface area and more exposed active sites for reactions [36,46]. EDS was also conducted to further confirm the composition of Mn 2 O 3 -Fe 2 O 3 /CFs (3:1).…”
Section: Characterization Of Mn 2 O 3 -Fe 2 O 3 /Cfsmentioning
confidence: 99%
“…Moreover, metal salts/polymer precursor fibers which are prepared via electrospinning may be converted into metal oxides loaded CFs after the thermal treatment in air. The films assembled by the metal oxides loaded CFs possess large specific surface area, high flexibility, massive exposed active sites and excellent conductivity to facilitate charge transfer and mass transfer [46,47].…”
Section: Introductionmentioning
confidence: 99%